Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T17:23:33+01:00
Zad 1
a) -3(y-2)+4(y+2) = -3y + 6 + 4y + 8 = y + 14
b) 5(x-y-1)-4(x+2) = 5x - 5y -5 -4x -8= x -5y - 13
c) 2(3a+b)-2(a-b) = 6a + 2b - 2a + 2b =4a + 4b

Zad 2
a)
-4x - 3
---------
23

b)
13x -9
-----------
23
2010-03-11T17:25:16+01:00
Zad1
a) -3y +6+4y+8=y+14
b) 5x-5y-5-4x-8=x-5y-13
c)6a+2b-2a+2b=4a+4b
2010-03-11T17:31:08+01:00
Ad1.
a)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
b)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
c)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b

Ad2.
Uprość podane wyrażenia
a)
2x+6 6x-9
____ - _____ = /*6
2 3

2x+6 6x-9
6* ____ -6* _____ =
2 3
6x+6-12x-9=-6x-3

b)
4* x-7 9 * x-1
__ + ___ = /*6
2 3

3*ax-7+2*9x-1= 30x-8